Analysis of the panoramic radiographic density of the mandibular bone in the elderly due to increased cortisol levels - Noor Rachmawati; Ria Noerianingsih Firman; Lusi Epsilawati; Merry Annisa Damayanti (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: Mandibular bone is generally formed by intramembranous ossification. Bone density mandible can be assessed from the trabecular pattern. In the elderly, the hormone cortisol affects bone formation through bone resorption by blocking calcium. The purpose of this study was to determine the correlation of cortisol levels to mandibular bone density in elderly women and men. Materials and Methods: This study was an analytic survey, where the population was determined from secondary patient data in the form of 31 panoramic radiographs and 31 laboratory results of cortisol examination, the research sample was divided into two groups. The bone density of the mandible was assessed from the trabeculae of the neck condyles region of the right and left. Density assessment using the ImageJ software program on panoramic radiographs was an examination that is often done in dentistry. Results: This study showed that the lowest density was in the group of women over 60 years. The results of the t-test with the independent sample obtained a p-value of > 0.05, which indicated there is no significant difference. The negative correlation value indicated that the relationship that occurs is opposite, p-value <0.05 which indicated the lower bone density, the higher cortisol level. Conclusion: Based on the results of the study, there was a correlation that with the increasing age of both women and men there was an increase in cortisol levels and a decrease in mandibular density.